2016
DOI: 10.4314/jasem.v19i4.2
|View full text |Cite
|
Sign up to set email alerts
|

Micellization of a Cationic Surfactant in Mixed Aqueous and Non-aqueous Solvent Systems

Abstract: ABSTRACT:The Micellisation behaviour of sodium dodecyl sulfate (SDS) in different mole fractions (0.1 0.5 and 0.9) of propylene glycol (PG) -water mixed solvents was investigated using electrical conductivity measurement at temperatures of 30, 35 and 40 0 C. The critical micelle concentration (CMC) increased and the degree of counterion dissociation values (α) decreased with increase in the composition of PG. Variation of CMC with temperature is marked with U-shaped curves while the degree of counterion dissoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The formation of micelles largely depends on the hydrophobicity of surfactants as well as solvent medium. Therefore, it is important to study the role of solvent media to understand the process of micellization. Previous studies on the cosolvent effect on the micellization process have been reported in terms of intermolecular interactions between water and cosolvent, and the results of such studies have been interpreted in terms of the water structure-making or structure-breaking ability of cosolvents . To study the effect of cosolvents on the micellization of ionic surfactants, two of the most common industrially important cosolvents, glycerol (polar protic) and DMSO (polar aprotic), have been selected.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of micelles largely depends on the hydrophobicity of surfactants as well as solvent medium. Therefore, it is important to study the role of solvent media to understand the process of micellization. Previous studies on the cosolvent effect on the micellization process have been reported in terms of intermolecular interactions between water and cosolvent, and the results of such studies have been interpreted in terms of the water structure-making or structure-breaking ability of cosolvents . To study the effect of cosolvents on the micellization of ionic surfactants, two of the most common industrially important cosolvents, glycerol (polar protic) and DMSO (polar aprotic), have been selected.…”
Section: Introductionmentioning
confidence: 99%
“…The CMC and the degree of dissociation are found to increase propositionally with the concentration of the cosolvent. However, Grace and Daniel et al showed that the CMC increased and the degree of counterion dissociation decreased with an increase in concentration of the cosolvent. Shirzad and Sadeghi looked at the impact of short-chain alcohols as cosolvents on micellization.…”
Section: Effect Of Cosolvent On Amino Acid–surfactant Interactionsmentioning
confidence: 99%
“…These surface-active molecules are used primarily as detergents, wetting agents, and softeners in soap manufacturing and pharmaceutical industries. Surfactants are classified as cationic (a positively charged head such as mono-alkyl quaternary systems), anionic (negatively charged hydrophilic head, for example, alkyl benzenesulfonates), and non-ionic (does not have an electrical charge), and investigations on amino acid–surfactant interactions have been present in the center of active research for the past few decades . Surfactants are wetting agents that lower surface tension and spread.…”
Section: Introductionmentioning
confidence: 99%